2009
DOI: 10.4049/jimmunol.0901666
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary IL-17E (IL-25) Production and IL-17RB+ Myeloid Cell-Derived Th2 Cytokine Production Are Dependent upon Stem Cell Factor-Induced Responses during Chronic Allergic Pulmonary Disease

Abstract: In the present studies local neutralization of allergen-induced stem cell factor (SCF) leads to decreased production of Th2 cytokines, a reduction in inflammation, allergen-specific serum IgE/IgG1, and attenuation of severe asthma-like responses. The local blockade of pulmonary SCF also resulted in a significant reduction of IL-17E (IL-25). Sorted cell populations from the lung indicated that IL-25 was produced from c-kit+ cells, whereas Th2 cytokine production was primarily from c-kit− cell populations. SCF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 47 publications
2
64
0
Order By: Relevance
“…Increased numbers of eosinophils in the tissues, blood and bone marrow is a hallmark of an allergic asthma phenotype and, in general, the elevated number of these cells correlates with disease severity [1]. Eosinophils have been identified as one of the main sources of IL-25 in Churg-Strauss syndrome patients [16], and in in vitro studies, IL-25 has also been reported to be derived from eosinophils [17,18]. Our study did not show a difference in the intracellular expression of IL-25 in eosinophils from that in asthmatic subjects; this may be explained by the dynamic release of IL-25 from eosinophils in allergic asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…Increased numbers of eosinophils in the tissues, blood and bone marrow is a hallmark of an allergic asthma phenotype and, in general, the elevated number of these cells correlates with disease severity [1]. Eosinophils have been identified as one of the main sources of IL-25 in Churg-Strauss syndrome patients [16], and in in vitro studies, IL-25 has also been reported to be derived from eosinophils [17,18]. Our study did not show a difference in the intracellular expression of IL-25 in eosinophils from that in asthmatic subjects; this may be explained by the dynamic release of IL-25 from eosinophils in allergic asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…IL-25 (IL-17E) was initially reported to be derived from highly polarized Th2 cells (Fort et al 2001;Reynolds et al 2010); however, further studies have demonstrated expression in IgE-activated mast cells (Ikeda et al 2003), alveolar macrophages (Kang et al 2005), microglia (Kleinschek et al 2007), eosinophils (Dolgachev et al 2009;Wang et al 2007), basophils ), epithelial cells Zaph et al 2008), and endothelial cells (Sonobe et al 2009). …”
Section: Il-25mentioning
confidence: 99%
“…IL-25 uses a heterodimeric receptor complex consisting of IL-17RB and IL-17RA (Rickel et al 2008) that is expressed on both innate and adaptive immune cells (Reynolds et al 2010), including NKT cells (Terashima et al 2008), eosinophils (Wong et al 2005), monocytes (Dolgachev et al 2009), and T cells (Iwakura et al 2011). Furthermore, human Th2 central memory cells selectively up-regulate receptor expression when stimulated with TSLP-activated dendritic cells or when triggered by a specific antigen ).…”
Section: Il-25mentioning
confidence: 99%
“…Administration of IL-25 was shown to induce IL-4, IL-5, and IL-13 production, even in the absence of B and T lymphocytes in recombination activating gene (Rag)-deficient mice [15]. The main sources of IL-25 in asthma are the lung epithelium, eosinophils, mast cells, and basophils [16]. Moreover, IL-25 amplifies Th2 responses and causes increased eosinophilic infiltration in mice [17].…”
Section: Introductionmentioning
confidence: 99%